计算(1)x+1分之x - x-1分之1 - x²-1分之2 (2)(x分之1+y分之1)² - (x分之1-y分之1)²(3)(x²-x-6分之x²-4 - x-3分之x+2)除以 x-3分之4
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/10 00:15:30
计算(1)x+1分之x-x-1分之1-x²-1分之2(2)(x分之1+y分之1)²-(x分之1-y分之1)²(3)(x²-x-6分之x²-4-x-3分
计算(1)x+1分之x - x-1分之1 - x²-1分之2 (2)(x分之1+y分之1)² - (x分之1-y分之1)²(3)(x²-x-6分之x²-4 - x-3分之x+2)除以 x-3分之4
计算(1)x+1分之x - x-1分之1 - x²-1分之2 (2)(x分之1+y分之1)² - (x分之1-y分之1)²
(3)(x²-x-6分之x²-4 - x-3分之x+2)除以 x-3分之4
计算(1)x+1分之x - x-1分之1 - x²-1分之2 (2)(x分之1+y分之1)² - (x分之1-y分之1)²(3)(x²-x-6分之x²-4 - x-3分之x+2)除以 x-3分之4
(1)x+1分之x - x-1分之1 - x²-1分之2
=[x(x-1)-(x+1)-2]/(x²-1)
=(x²-x-x-1-2)/(x+1)(x-1)
=(x-3)(x+1)/(x+1)(x-1)
=(x-3)/(x-1)
(2)(x分之1+y分之1)² - (x分之1-y分之1)²
=(1/x+1/y+1/x-1/y)(1/x+1/y-1/x+1/y)
=2/x×2/y
=4/xy
(3)(x²-x-6分之x²-4 - x-3分之x+2)除以 x-3分之4
=[(x+2)(x-2)/(x-3)(x+2)-(x+2)/(x-3)] ×(x-3)/4
=[(x-2)/(x-3)-(x+2)/(x-3)]×(x-3)/4
=-4/(x-3)×(x-3)/4
=-1
计算 x-1分之1 - x²-1分之x
计算:x-1分之x+1-x分之1
x+1分之3-x+1分之3x 计算
计算:{x+1-(1-x分之1)} /{x-(x-1分之x的平方)
分式计算:x分之x²-1乘x+1分之x+(3x+1)
计算:(x-y)分之2+y分之x-x分之1
计算x(x-1)分之1+(x-1)(x-2)分之1+(x-2)(x-3)分之1+...+(x-99)(x-100)分之1
计算 x-2分之x方+1-2-x分之3-4x (x+y)x方-y方分之x方+y-x分之y方
计算x平方+x+1+1-x分之x立方
计算:x分之x+1 × (x+1分之2x)² - (x-1分之1 - x+1分之1)
(x+2分之x+3)-(x+1分之x+2)=(x+4分之x+5)-(x+3分之x+4) 计算x+3分之2x+9-x-3分之1
计算 :x-3分之1+(9-x^2)分之6-(6-2x)分之(x-1)
x^2-4分之2x-2-x分之1+x+2分之3计算
计算(x分之1)-(3x分之2)+(3x-2分之x)
计算 【(x+1)分之(x-1)-(x+2)分之(x+1)】/(x的平方+4x+4)分之(x+3)
计算1-x分之1+1+x分之1
(x²-2x)分之(x+2)-(x²-4x+4)分之(x-1) 计算
(x²-2x)分之(x+2)-(x²-4x+4)分之(x+1) 计算